Attitudinal Realization to Unmask the Ideology behind Prabowo’s Speech at the UNGA80 - Suswanto Ismadi Megah S; Sri Sugiharti; Zulida Abdul Kadir; Ismael Hasan Alsanafi; Saira Kazmi (UIN Raden Mas Said Surakarta, 2026)
This study adopted an analytical combination of Critical Discourse Analysis (CDA) and Systemic Functional Linguistics (SFL), particularly Appraisal theory of Martin & White (2005), to achieve the objective of the study. The categorization of Appraisal analysis in each lexical choice has been investigated under the Attitudinal system with its three subtypes: Judgement, Affect, and Appreciation. This research design employed a mixed-method approach, integrating both qualitative and quantitative methodologies, with the qualitative method aimed at describing the data and the frequencies of the lexical choices obtained from the quantitative method. The qualitative aspect is indicated by the application of CDA. The results show that President Prabowo’s intentional ideology toward the chronic issue of Palestine-Israel is positioning the main actors through evaluative expressions in his emotional speech delivered at the United Nations General Assembly 80th Session, in New York. It is found that the most dominant frequency comes to the subtype of appreciation, particularly valuation, rather than all subtypes of attitudinal types. This indicates that President Prabowo ideologically, directly, and positively appreciates the world leaders in supporting and cooperating to solve the Palestine-Israel conflict with a two-state solution. Socio-culturally, Muslims make up the majority of the Indonesian population, more than 80%, and historically, Indonesia and Palestine have a long-standing relationship. Indonesia will recognize Israel if Israel does the same to Palestine.